2011
DOI: 10.1002/hfm.20295
|View full text |Cite
|
Sign up to set email alerts
|

Various approaches to a human preference analysis in a digital signage display design

Abstract: This article is concerned with various ways of analyzing the subjective assessment of displaying digital signage content. In the beginning, the brief description of the signage system evolution is described; next, the carried out experiment is depicted. The preferences of the 32 subjects were obtained using pairwise comparisons of the designed screen formats. Then the priorities were derived by applying the Analytic Hierarchy Process framework. The gathered data were modeled and analyzed by means of the analys… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…For example, the mean CR values regarding various graphical conditions [16,22,23] exhibit great differences. Thus, the overall average CR in [17] was almost twice the mean CR in [26]. The results in [26] also show that even small changes in the experimental context may affect the consistency because the same participants were markedly less consistent before performing efficiency testing compared with that after executing the experimental task.…”
Section: Consistency Of the Comparison Ratings Matrix Vs The "Qualitmentioning
confidence: 71%
See 2 more Smart Citations
“…For example, the mean CR values regarding various graphical conditions [16,22,23] exhibit great differences. Thus, the overall average CR in [17] was almost twice the mean CR in [26]. The results in [26] also show that even small changes in the experimental context may affect the consistency because the same participants were markedly less consistent before performing efficiency testing compared with that after executing the experimental task.…”
Section: Consistency Of the Comparison Ratings Matrix Vs The "Qualitmentioning
confidence: 71%
“…The possibility of obtaining high consistency in terms of the CR value depends greatly on many factors. For example, Grobelny and Michalski [17] and Michalski [25] showed that the gender of subjects had a significant effect on the CRs. These studies showed that females were generally less consistent than male participants.…”
Section: Consistency Of the Comparison Ratings Matrix Vs The "Qualitmentioning
confidence: 97%
See 1 more Smart Citation
“…We also computed consistency ratios for every subject to assess the degree of comparisons validity. Specifics regarding computations of preferences' weights and consistency ratios may be found, for instance, in the paper of Grobelny and Michalski (2011) or Michalski (2011). …”
Section: Variables and Experimental Designmentioning
confidence: 99%
“…Little and Briggs (2009) address the problem of receiving personal information in public spaces via personalized interaction. Grobelny and Michalski (2011) focus on digital signage content design. By performing pairwise human preferences comparison analysis, they show that different layout structures, background and content positioning can significantly affect the user's perception of the digital signage content.…”
Section: Introductionmentioning
confidence: 99%